Exploring the experiences of Education Welfare Officers engaging with cases of persistent pupil absence from school: a Grounded Theory study - Horne, Jilly (2012)
Using a grounded theory approach within a social constructivist epistemology, the research study explores the experiences of Education Welfare Officers (EWOs) engaging in assessment and intervention with cases of persistent absence from school. Whilst much of the discussion related to non attendance has focused on risk and causation factors, categorisation and the effectiveness of specific interventions, there is limited research which has specifically focused on the practice of the EWO as the initial and often only agency to try to engage with this vulnerable group of children, young people and their families. The research design involved interviewing 14 members of an Education Welfare Service (EWS) and engaging in a qualitative interpretive analysis of the interview data, in line with the suggested grounded theory phases of analysis. Utilising the theoretical perspectives of Social Cognitive Theory, specifically focusing on self efficacy beliefs, together with Systems and Attribution theories, the Grounded Theory offers an insight into the significance and effects of EWO self efficacy beliefs on their own practice and how systemic influences, such as those offered by the school, family and other agencies, including the EWS, can either support or hinder EWO assessment and intervention processes.